Evaluating performance and emissions of a CI engine fueled with n-octanol/diesel and n-butanol/diesel blends under different injection strategies. (15th January 2021) - Li, Jing; Yu, Wenbin; Yang, Wenming
Abstract: Considering climate change and energy crisis, the high-carbon alcohol has become a popular substitute fuel for diesel engines. In this study, diesel (D100), n-octanol/diesel (D50O50), and n-butanol/diesel (D50B50) blends were tested in a single-cylinder CI engine to evaluate the effects of n-octanol and n-butanol on the engine combustion characteristics, performance, and emissions formation. During the testing, the engine was operated at two engine loads (30% and 50%) with two injection pressures (40 and 60 MPa) at 1200 rpm. Both single injection and split injection strategies were used. Experimental results suggest that D50O50 and D50B50could result in serious knocking combustion under certain conditions with the single injection strategy. In contrast, the split injection strategy can lower the peak pressure and peak heat release rate, and consequently mitigating the knocking tendency for D50O50 and D50B50. Besides, noticeable two-stage combustion was observed for D100 and D50O50 due to the NTC behavior of diesel and n-octanol. Generally, because of the lower fuel reactivity of n-octanol and n-butanol, the ignition delay periods of D50O50 and D50B50 were significantly extended with the single injection; however, the difference in ignition delay was not evident with split injection strategy. Moreover, D50O50 can exhibit the highest thermal efficiency with proper injection pressure, and combustion phasing, etc. NOx and black carbon can be simultaneously reduced by D50O50 with split injection at an injection pressure of 60 MPa. Nevertheless, adding n-octanol and n-butanol increased the HC emissions due to their lower fuel reactivity at all tested conditions.